2023
DOI: 10.3390/cells12071083
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Preformed Fibrils Bind to β-Neurexins and Impair β-Neurexin-Mediated Presynaptic Organization

Abstract: Synucleinopathies form a group of neurodegenerative diseases defined by the misfolding and aggregation of α-synuclein (α-syn). Abnormal accumulation and spreading of α-syn aggregates lead to synapse dysfunction and neuronal cell death. Yet, little is known about the synaptic mechanisms underlying the α-syn pathology. Here we identified β-isoforms of neurexins (β-NRXs) as presynaptic organizing proteins that interact with α-syn preformed fibrils (α-syn PFFs), toxic α-syn aggregates, but not α-syn monomers. Our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Microglial engulfment may not be the sole cause of synapse degeneration during α-synuclein propagation. Other studies have suggested that PFF also impacts the formation and molecular organization of presynaptic terminals by inhibiting βneurexin [34] or by decreasing the levels of soluble α-synuclein [35]. However, it is worth noting that the latter studies examined the direct effects of PFFs on neurons in culture, whereas our study assessed the effects of α-synuclein propagation throughout a neural network in an intact-tissue environment.…”
Section: Discussionmentioning
confidence: 92%
“…Microglial engulfment may not be the sole cause of synapse degeneration during α-synuclein propagation. Other studies have suggested that PFF also impacts the formation and molecular organization of presynaptic terminals by inhibiting βneurexin [34] or by decreasing the levels of soluble α-synuclein [35]. However, it is worth noting that the latter studies examined the direct effects of PFFs on neurons in culture, whereas our study assessed the effects of α-synuclein propagation throughout a neural network in an intact-tissue environment.…”
Section: Discussionmentioning
confidence: 92%
“…This interaction was reported to initiate α-synuclein PFF endocytosis, transmission, and neuronal cell toxicity ( 16 ). However, this study did not rule out possible contributions by other α-synuclein PFF binding partners, for example, neurexin 1β ( 63 ). In addition, a more recent study found no evidence of LAG3 expression in neurons or of a role for LAG3 in modulating α-synucleinopathies ( 64 ).…”
Section: Structure Of Lag3mentioning
confidence: 87%
“…Purification of α-syn was described previously by Feller et al 103 . In brief, the pGEX-6P-1 plasmid (University of Dundee MRC Protein Phosphorylation and Ubiquitination Unit, DU30005) cloned with full-length human wild-type α-syn was transformed to BL-21(DE3) E.coli.…”
Section: Methodsmentioning
confidence: 99%
“…Then PFF was sonicated at least 40 cycles of 30-sec on/30-sec off using a Bioruptor ® Pico sonication unit (Diogenode, B01020001). Samples (∼20 μL) were reserved for PFF quality control by thioflavin T assay, dynamic light scattering (using Zetasizer Nano S, Malvern, DLS assay) and TEM imaging as described 103 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation